2022
DOI: 10.52609/jmlph.v2i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bi-lingual Multidisciplinary Simulation-based Training in Improving Communication and Breaking Bad-News Skills

Abstract: Background: Healthcare worker (HCW)-patient communication is an essential element of every patient’s journey, and evidence links good communication with favourable patient experiences and outcomes. Simulation-based training (SBT) is a promising and effective tool to improve such communication. Aim: To develop a bilingual SBT programme in communication skills for all HCWs in an academic tertiary hospital, to improve patient care, experiences and outcomes. Methods: This was a quasi-experimental design, conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In many situations, like intensive care units or emergency wards, nurses might be the first to face the task. They are involved before, during, and after the bad news is created and can help patients prepare for receiving bad news and cope with the distressing conditions (10,11). Studies have shown that being actively involved in this process improves patient-nurse relationships (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In many situations, like intensive care units or emergency wards, nurses might be the first to face the task. They are involved before, during, and after the bad news is created and can help patients prepare for receiving bad news and cope with the distressing conditions (10,11). Studies have shown that being actively involved in this process improves patient-nurse relationships (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%